Insulating Property Improvement of Polyimide in Devices by Low‐Temperature Supercritical Fluids. (9th September 2019) - Li, Lei; Chang, Kuan‐Chang; Lin, Xinnan; Zhang, Rui; Lou, Jyun‐Hao
Abstract: Low‐temperature supercritical fluids technology is applied in this study to improve the insulating property of the polyimide film in electronic devices. Supercritical CO2 fluids take the residual small molecules out of high molecular polymers at low temperature in a short time, which can eliminate the defects in polyimide films and improve the insulating property. The metal–insulator–metal capacitor devices with polyimide as the dielectric layer are fabricated for investigation. The electrical measurements of devices indicate an eight times reduction of the leakage current after supercritical CO2 treatment and the electrical conduction mechanism is changed from Poole–Frankel to Schottky mechanism. Additionally, the material analysis by Fourier transform infrared spectroscopy (FTIR) of the polyimide film is conducted to confirm that the residual molecules are removed after supercritical CO2 fluids treatment. This study shows a promising methodology for supercritical fluids to treat polyimide films in electronic devices, which expands more potential applications of polyimide films in the semiconductor field. Abstract : Supercritical fluids treatment can remove the residual molecular solvent in polyimide films and eliminate the defects. As a result, the insulating property of polyimide films is improved and the leakage current of electronic devices is significantly reduced.